Analisis Faktor Ruangan yang Berpengaruh Terhadap Nilai Tanah Perkotaan - Hening Widi Oetomo (Universitas Islam Indonesia, 2006)
Urban Land value have increased tendency but building value have decreased tendency. It is important to know what’s factor influencing the land value.The method for addressing the above-mentioned problem is factor analysis. Data collected from a sample of 1558 lots in Surabaya and there are 16 variables used in this study. There are grouping into 3 category, first structural factor, neighborhood factor and location factor. The results of factor analysis, there are 13 variables usable and grouped into five new factor based on eigen value more than 1 (>=1). The five factors are: Social Factor has eigen value of 3.142 with variant percentage of 19.64 %; Phisical Factor has eigen value of 2.346 with variant percentage of 14.663 %; Economic Factor has eigen value of 1,633 with variant percentage of 10.206 %; Education Factor has eigen value of 1,182 with variant percentage of 7.388 %; Construction Factor has eigen value of 1,054 with variant percentage of 6.589 %. From correlation matrix, we get value from Bartlett’s Test of Sphericity (BTS) of 7204.552, which suggest that on correlation matrix, there are correlation between factors supported by Kaiser-Meyer-Olkin (KMO) value of 0,612 and variant cumulative value of 58.486 %.The Social Factor consists of 3 variables, namely number of secondary school in radius 1 miles (N4), number of worship in radius 1 miles (N7) and nearest distance to Central Business District (L1). The Phisical Factor consists of 3 variables namely shape index (S4), flooded classes (N1) and road classes (N2). The Economic Factor consists of 2 variables namely nearest distance to public market (L2) and nearest distance to electric pole (L3). The Education Factor consists of 3 variables namely number of elementary school in radius 0.25 miles (N3), nearest distance to elementary school (N5) and nearest distance to secondary school (N6). The Construction Factor consist of 2 variables namely area (S1) and front width (S2).Based on the results, all of institution such as banking, taxation, real estate enterprise which correlation with the land value, suggested to monitoring the factor has founded in this researh for appraisal of land value in Surabaya. Keywords: urban land value, hedonic concept, factor analysis